Laparoscopic surgery; Stepping into a clip-less cholecystectomy era - Mohammad Osama; Sarfaraz Khan; Nawazish Ali (Journal of the Pakistan Medical Association, 2025)
Dear Editor, The introduction of laparoscopy to the surgical art is not new. Over the past few decades, operative laparoscopy has experienced remarkable advancements, enabling numerous complex procedures to be performed through this minimally invasive approach. Following its initial challenges, laparoscopic surgery has matured, evolving into a phase of gradual refinement, making it challenging to predict its future trajectory and long-term outcomes. However, in a resource limited country like Pakistan, the full implementation and acceptance of this new surgical technique comparable to the conventional Open approach is still questionable, pertaining to different causes like general population public awareness and economic constraints. The provision of laparoscope by government in our institution at MTI Gomal Medical College has revolutionized the standard of care but it has some shortcomings too, in the form of structured training programmes for the surgical staff, inconsistencies in instrument standardisation, affordability and public acceptability. Different surgical procedures are being performed at our institution, Cholecystectomy being the most common. Laparoscopic cholecystectomy as gold standard offers better outcomes than open cholecystectomy, with less pain, shorter hospital stays, and quicker recovery, but requires advanced infrastructure and costly equipment. In a few cases of laparoscopy cholecystectomy performed at our setup, the surgical team faced the problem of post-operative complications, including infection and bile leakage. During laparoscopic cholecystectomy, metallic clips are typically used to ligate the cystic duct and artery, However, complications such asclip slippage, a foreign body reaction that and, in rare cases, hypersensitivity reactions1, the clips becoming a nidus for infection, and a remote possibility of clip erosion in surrounding structures if dislodged. Vessel sealing technologies, such as LigaSure and Harmonic scalpel, offer promising alternatives for cystic artery control and haemostasis, yet their high cost poses a significant barrier in low-resource setting. Additionally, the use of these energy devices is questionable for the control of extra-hepatic biliary channels. The alternative to these metal clips is absorbable suturing material such as Vicry l. Different studies have looked into the safety and feasibility of cystic duct control with suture ligation during laparoscopic cholecystectomy2-4. A study by Akhtar et al. concluded that biliary leakage occurs more frequently with clipped laparoscopic cholecystectomy for cholecystitis, supporting the adoption of clip-less technique in select patients to minimize complications and optimize patient outcomes5. ---Continue